Hubungan Antara Tingkat Pengetahuan Mobilisasi Dini Dengan Perilaku Mobilisasi Dini Pasien Post Operasi Apendik: Relationship Between Knowledge Level of Early Mobilization with Early Mobilization Behavior of Patients Post Pendic Surgery - Kasmir (Dohara POAJ, 2021)
Introduction: One of the postoperative client care is to make the mobilization. Mobilizing exercises are carried out to prevent complications, prevent pressure sores, stimulate peristalsis and reduce pain. Methods: The design of this study is a descriptive correlative study which aims to determine the relationship between the level of knowledge and motivation of nurses on the provision of early mobilization. The population of this research is the appendic patient at RSAL Dr. Mintohardjo. The sample in this study was total sampling, with a sample of 59 respondents. The instrument uses an observation sheet. Results: The results showed that the value of P value = 0.007 means P value <0.05, so it can be concluded that there is a significant relationship between the respondent's level of knowledge and early mobilization behavior. Discussion: There is a significant relationship between the respondent's level of knowledge and early mobilization behavior.